G protein-coupled receptors as promising cancer targets. Issue 2 (1st July 2016) - Liu, Ying; An, Su; Ward, Richard; Yang, Yang; Guo, Xiao-Xi; Li, Wei; Xu, Tian-Rui
Highlights: GPCR dysregulation can cause cancer, but the role of GPCRs in carcinogenesis has been largely ignored. The latest developments suggest that GPCRs are among the most useful targets against diverse malignant cancers. The ligands targeting GPCRs may provide effective cancer therapeutics and some anticancer compounds have entered clinical trials. Abstract: G protein-coupled receptors (GPCRs) regulate an array of fundamental biological processes, such as growth, metabolism and homeostasis. Specifically, GPCRs are involved in cancer initiation and progression. However, compared with the involvement of the epidermal growth factor receptor in cancer, that of GPCRs have been largely ignored. Recent findings have implicated many GPCRs in tumorigenesis, tumor progression, invasion and metastasis. Moreover, GPCRs contribute to the establishment and maintenance of a microenvironment which is permissive for tumor formation and growth, including effects upon surrounding blood vessels, signaling molecules and the extracellular matrix. Thus, GPCRs are considered to be among the most useful drug targets against many solid cancers. Development of selective ligands targeting GPCRs may provide novel and effective treatment strategies against cancer and some anticancer compounds are now in clinical trials. Here, we focus on tumor related GPCRs, such as G protein-coupled receptor 30, the lysophosphatidic acid receptor, angiotensin receptors 1 and 2, the sphingosine 1-phosphate receptors and gastrin releasing peptide receptor. We also summarize their tissue distributions, activation and roles in tumorigenesis and discuss the potential use of GPCR agonists and antagonists in cancer therapy.